188k views
4 votes
PLS SOLVE WITH EXPLANATION

-4(v + 1) = 2v-2 +2(3v + 2)

Make sure you simplify it as much as you can!​

User Nilamo
by
5.2k points

2 Answers

3 votes

The answer to your problem is
V=-1/2
I simplified as much as I could possibly
User Danielpiestrak
by
5.5k points
3 votes

Answer:

v = -1/2

Explanation:

-4(v+1) = 2v - 2 + 2(3v + 2)

-4v - 4 = 2v - 2 + 6v + 4

-4v - 4 = 8v + 2

-4 = 12v + 2

-6 = 12v

-6/12 = v

v = -1/2

User Exophase
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.